Curricular integration of outreach in higher education: curricularized pedagogical dynamics - Garcia, Marisa Daniella Oliveira (2024)
The Principle of Inseparability between Teaching, Research, and Extension, as expressed in the Federal Constitution, is a guideline for the functioning of Higher Education Institutions (HEIs). However, Extension still needs to advance administratively and academically within educational institutions, whether due to difficulties in securing a place in their administrative structures or the fragile position it finds in various academic trajectories. In the context of this debate about the need to value Extension in HEIs, as well as the necessary connection of Institutions with society, the National Education Plan (NEP) has provided for the mandatory integration of extension actions in the curriculum of undergraduate courses. Therefore, this study aims to present a pedagogical dynamic of curricularization of extension in higher education that enables the development of interactivity, connectivity, and interdependence among all cultural phenomena, being understood and presented as a permanent dialogue with the world of work.